Multiscale Three-Dimensional Morphological Characterization of Calcareous Sand Particles Using Spherical Harmonic Analysis - Liang, Hui; Shen, Yang; Xu, Junhong; Shen, Xue (Frontiers in Physics, 2021)
Particle morphology is a fundamental inherent property that substantially affects the macroscopic behavior of granular materials. The division and separation of particle morphology at different scale levels contributes to the further multiscale morphology related orthogonal researches. In this context, the high-resolution X-ray micro-computed tomographic (X-CT) scanning and spherical harmonic (SH) analysis were combined to complete the precise and digitized reconstruction of sand particles. The 3D sphericity, roundness and roughness were introduced to define the particle morphology at three scale levels (the general shape, local angularity and surface textures). Two typical sand particles, Calcareous sand (CS) and Fujian sand (FS), were tested in this study. The results showed that the irregularity, angularity and roughness of CS is higher than that of FS, and the multiscale morphological features of the two types of natural sand were given and compared digitally.